2018
DOI: 10.1038/s41419-017-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EHMT2 reverses EGFR-TKI resistance in NSCLC by epigenetically regulating the PTEN/AKT signaling pathway

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) resistance is a major obstacle in the treatment of non-small cell lung cancer (NSCLC). Epigenetic alterations have been shown to be involved in NSCLC oncogenesis; however, their function in EGFR-TKI resistance remains uncharacterized. Here, we found that an EHMT2 inhibitor, UNC0638, can significantly inhibit cell growth and induce apoptosis in EGFR-TKI-resistant NSCLC cells. Additionally, we also found that EHMT2 expression and enzymatic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Our results demonstrate that G9a not only sustains oncogenic signaling in the tumors, but also blocks their ability to undergo myogenic differentiation. Our data are consistent with a recent study that showed G9a-mediated repression of PTEN expression in non-small cell lung cancer (43). Previous studies have shown that the PI3K/AKT signaling is elevated in ARMS.…”
Section: G9a Knockdown Inhibits Tumorigenicity In Vivosupporting
confidence: 94%
“…Our results demonstrate that G9a not only sustains oncogenic signaling in the tumors, but also blocks their ability to undergo myogenic differentiation. Our data are consistent with a recent study that showed G9a-mediated repression of PTEN expression in non-small cell lung cancer (43). Previous studies have shown that the PI3K/AKT signaling is elevated in ARMS.…”
Section: G9a Knockdown Inhibits Tumorigenicity In Vivosupporting
confidence: 94%
“…112 In addition, it has been shown that CpG hypermethylation mediates the epigenetic silencing of PTEN in lung cancer cells, causing acquired resistance to first-generation EGFR-TKIs. 113 Wang et al 114…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%
“…With the continuous exploration of the pathogenesis of NSCLC, more and more molecules have been found to be enrolled in the occurrence and progression of this disease. 18,19 Previous studies have found that FSTL family members have abnormal expression in tumors and are involved in the tumorigenesis and cancer progression. For example, FSTL1 expression is down-regulated in NSCLC, and its overexpression can significantly inhibit cell proliferation, migration and invasion, and induce apoptosis, 20 while FSTL1 expression is up-regulated in hepatocellular carcinoma, and knocking down its expression can promote apoptosis and inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%